2020
DOI: 10.1186/s13023-020-01568-5
|View full text |Cite
|
Sign up to set email alerts
|

The urgent need to empower rare disease organizations in China: an interview-based study

Abstract: Background Each rare disease only affects a small number of population. However, a total of 7000 rare diseases may affect 10% of the population. Due to the severity and lack of rare disease awareness, rare disease represents a huge challenge for the healthcare system. In Western countries, patient organizations have been playing an integral role in raising awareness, advocating legislation, and supporting drug development. This study aims to assess the unmet needs of rare disease patient organizations in China… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…One major reason for the di culty in diagnosis is the limited rare disease awareness among patients, families, and physicians. Similar to a previous study in Europe 31 , as believed by patients and care-givers in this study, physicians did not have su cient awareness and knowledge about rare diseases. A recent study among physicians in China also showed a lack of rare disease awareness 32 .…”
Section: Discussionsupporting
confidence: 80%
“…One major reason for the di culty in diagnosis is the limited rare disease awareness among patients, families, and physicians. Similar to a previous study in Europe 31 , as believed by patients and care-givers in this study, physicians did not have su cient awareness and knowledge about rare diseases. A recent study among physicians in China also showed a lack of rare disease awareness 32 .…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, the duration between onset and diagnosis in China was 1.4 years, and there were only 1.8 misdiagnoses. This may be because of the increased application of newborn screening over the years in China [31]. It may be also because social media has increased avenues for relevant information and communication between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although newborn screening has undergone a rapid development, it is still a great challenge to increase coverage and expand disease panel across the whole country [ 9 ]. Partially due to efforts of many patient organizations, rare disease awareness in China increased significantly [ 10 ]. Further, China released its first official list of 121 rare diseases in 2018, representing an initial and essential step.…”
Section: Introductionmentioning
confidence: 99%